Employment and vocational skills among individuals with autism spectrum disorder: predictors, impact, and interventions - LYDON, SINEAD; HEALY, OLIVE (Springer, 2014)
Much research has been devoted to early intervention for individuals with Autism Spectrum Disorder (ASD), with a lesser emphasis on research examining the outcomes for, or support of, these individuals as they reach employment-age. Historically, employment opportunities for individuals with ASD have been limited. The current literature review sought to investigate the existing predictors and impact of employment or vocational placements among persons with ASD. Interventions described in the literature to teach individuals with ASD employment or vocational skills were also assessed. A total of 26 studies were reviewed and results indicate that there is limited extant research on employment and vocational skills among individuals with ASD. However, it was found that employment positively impacted on the quality of life, cognitive functioning and well-being of participants with ASD. Predictors of employment were found to be a complex interplay of personal and external factors. All interventional studies reported improvements in the vocational skills targeted although a limited range of skills have been taught across these studies. The implications of these findings for individuals with ASD and future research in this area are discussed.
PUBLISHED
Keywords: work; vocational skills; employment; developmental disabilities; Asperger’s syndrome; autism spectrum disorder